EVALUATION OF MOTOR FUNCTION OF STOMACH IN CHILDREN WITH GASTROESOPHAGEAL REFLUX - A.M. Zaprudnov; N.V. Butorina; Ya.M. Vakhrushev ("Paediatrician" Publishers LLC, 2010)
Authors examined 62 children with gastroesophageal reflux (GER), 39% of these children were in pre-pubertal period (9-12 years old) and 61% - in pubertal period (13-17 years old). Electrogastrography (EGG) performed in the morning on an empty stomach during 15-20 min showed that children 9-12 years old predominantly have tachigastria (5.8 ± 2.4 cycle/min). In children 13-17 years old bradigastria (1.6 ± 1.0 cycle/min) was more common (in 68% of children). Amplitude of waves in children 9-12 years old was similar to hyperkinetic type of EGG (55.4 ± 15/7 mm). 68% of children 13-17 years old had hypokinetic type of EGG with wave amplitude 18.4 ± 7.5 mm. Thus, the study showed that disorders of motoric function of stomach are different in different age. Children in pre-pubertal period have hyperkinetic activity or gastric muscles, and in pubertal period GER is characterized by low frequency and amplitude of gastric contractions. Key words: children, adolescents, gastroesophageal reflux disease, motor function of stomach, electrogastrography.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):14-15)